We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
93
1
avatar

Solve for m. -3 + m 9 = 10 A. -30 B. 63 C. 87 D. 93

 Mar 22, 2019

Best Answer 

 #1
avatar
+1

 

Solve for m. -3 + m 9 = 10 A. -30 B. 63 C. 87 D. 93 

 

I can't make sense of the problem as written. 

 

But, IF the problem were written as (–3 + m) / 9 = 10

 

then it follows that     –3 + m = 90                          multiplied both sides by 9 

and                                   m = 90 + 3  =  93          subtracted –3 from both sides 

 

.

 Mar 22, 2019
 #1
avatar
+1
Best Answer

 

Solve for m. -3 + m 9 = 10 A. -30 B. 63 C. 87 D. 93 

 

I can't make sense of the problem as written. 

 

But, IF the problem were written as (–3 + m) / 9 = 10

 

then it follows that     –3 + m = 90                          multiplied both sides by 9 

and                                   m = 90 + 3  =  93          subtracted –3 from both sides 

 

.

Guest Mar 22, 2019

9 Online Users

avatar